Biomarkers of Allogeneic Cell Therapy in Acute Steroid-Refractory Graftversus- Host Disease - Gonen-Yaacovi, Gil; Segurado, Oscar (Archives of Clinical and Medical Case Reports, 2021)
Cell therapy requires precise screening and monitoring of patients to ensure that the transfer of either autologous or allogeneic cells to a patient results in a therapeutic effect to targeted organs or tissues. One well-established application of cell therapy is allogeneic hematopoietic stem cell transplantation (allo-HSCT) to treat hematologic conditions. A common complication following allo-HSCT, however, is the development of acute graft-versus-host disease (aGVHD), which leads to substantial morbidity and mortality. There is currently no widely effective treatment for aGVHD, but cell therapy using decidua stromal cells (DSCs) has shown success in academic-driven clinical studies. The introduction of selective biomarkers of cellular, immune, and disease response to DSCs can help select the right patient, the right treatment, and the right monitoring in the treatment of aGVHD. In this article, we discuss the relevance of precision medicine as an essential approach to leverage biomarkers as well as other clinical aspects that optimize safety and efficacy of cell therapy in aGVHD.